Management of 6 Months old Neglected Talus Neck Fracture: A Case Report with Review of Literature - Moger, Nagaraj Manju; Pragadeeshwaran J; Sarkar, Mosharaf Hossain; Meena, Pradeep Kumar (Asian Journal of Medical Research, 2020)
Talus fractures are very rarely seen and account for approximately 1 percent of fractures around the foot and ankle Talar neck fractures are likely to damage the anastomotic ring, resulting in disruption of blood supply to the talar body which leads to significant problems in fracture healing and integrity. Approximately 39 percent of midfoot and ankle fractures could be missed during initial evaluation due to a lack of adequate radiological and clinical examination. Among these missed injuries approximately 50 percent are talus fractures. A 23-year-old male patient came with complaints of pain over the left foot while walking for 6 months. He had a history of falls from 10 feet height 6 months back. He was conservatively managed in a local hospital without any proper diagnosis. He presented to us 6 months later with chronic, dull aching, continuous pain which aggravates while walking and standing. The diagnosis of the non-union fracture neck of talus was made after radiology and was managed by open reduction and internal fixation with cannulated cancellous screws along with ipsilateral iliac crest cancellous bone grafting. Lack of timely diagnosis escalates the vascular insult, delays timely intervention, and increases morbidity.